Ácido ferúlico como potencial terapêutico no tratamento da obesidade: uma revisão integrativa - Bolconte, Raquel Lima (2022)
Overweight and obesity are responsible by the World Health Organization as the excessive accumulation of fat that presents to health, being for millions of deaths per year, is not limited to gender or age, becoming one of the most important concerns for global public health in the 21st century. Obesity represents an important risk factor for the development of other chronic diseases such as: diabetes, metabolic syndrome, cardiovascular diseases, unhealthy liver steatosis, degenerative diseases and more recently Covid-19. Some drugs are already used in the drug treatment of obesity, but in the long term they have several side effects. Thus, it is important to search for new drugs that are efficient in the treatment of obesity. Ferulic acid has been shown to be a potential therapeutic agent, having been previously reported for having several beneficial activities to human health, including antioxidant and anti-inflammatory activities, in addition to lowering cholesterol, which makes it an interesting object of study in the treatment of obesity. Therefore, this research aims to develop an integrative review of studies with ferulic acid in obesity. Initially, a research was carried out through a search in three databases: science direct, scielo and pubmed, in the period of 2021. For the selection of articles, the following inclusion criteria were adopted: experimental research articles with full texts, in English, between the years 2015 and 2020. In addition, the articles should present rodents as an animal model, and display in their title the descriptors: “ferulic acid obesity” and “ferulic acid fat”. The search was performed using the Boolean operator “AND” to associate the descriptors in the three databases. The exclusion criteria were based on the sucupira platform to evaluate the indexed journals published by the databases; articles with Qualis between A1 to B2, in the area of biotechnology, were chosen. In addition, articles that did not present the dose of ferulic acid used in the text were excluded. Through the search in the databases, it was possible to find 2,285 articles, but after a refinement of the studies, only 11 articles were selected. The main information of the articles was extracted and included in a qualitative synthesis presenting information and the main results of the articles. It was observed that oral supplementation of ferulic acid in rats can reverse almost all deleterious changes in animals studied; through insulin sensitization, with the aid of TNFα suppression and reduction of serine phosphorylation of IRS-1, PKCε, PTP1B, improving the lipid profile, reducing cholesterol and triglyceride levels. In addition, diabetic animals treated with ferulic acid showed increased glucose and insulin. Treatment with ferulic acid inhibits cell differentiation of adipocytes of the 3T3-L1 lineage; significantly reduces body weight gain, lipid level and adipose tissue mass in mice fed a hypercaloric diet; through downregulation of PPARy2, C/EBP-α and SREBP-1c levels. In addition, ferulic acid increases glycerol release from differentiated adipocytes; by activating lipolysis. Thus, these results suggest that ferulic acid has anti-obesity activity, being considered a therapeutic potential in the treatment of obesity and its complications.